Evaluation of Management of the UAPF Pension Assets Based on the Method of Multidimensional Clustering - ZHANTAYEVA, Aigul Abitzhanovna; ASSILOVA, Aizhan Sarsenovna; ATCHABAROVA, Aigul Malibekovna; MURATOVA, Diana Baltabaevna; AMALBEKOVA, Gulmira (Journal of Advanced Research in Law and Economics; Vol 7 No 6 (2016): Vol 7, No 6(2016): JARLE, Volume VII, Issue 6(20), Fall 2016, 2017)
Against the background of the financial crisis, all the shortcomings in the management of pension assets have become apparent, and not only in Kazakhstan. The authors have calculated the possible options of forming the funding structure of pension assets, which would satisfy the different age generations of investors in Kazakhstan. For the calculation, the methods of the multivariate statistical analysis and the quasi-Sharpe optimization model were used. Based on these results, the authors have proved the need of introducing additional components, which would insure the collateral risks of adequate pension payments.
Keywords: pension assets; multidimensional clustering; securities